Study of Management Diversity Based on Biographical Characteristics in Higher Education - Rustiana, A; Rahmaningtyas, W (KnE Social Sciences, 2018)
This study aimed to describe the diversity based on biographical characteristics in the Department of Economic Education. Informants consisted of lecturers and faculty leaders. The research method used qualitative approach with participant observation to see natural phenomenon and social activity. Data collection techniques used observation, documentation, interviews and document analysis. Activities in data analysis were data reduction, display data, and conclusion drawing / verification. Data validity applied source and methodological triangulation. The results showed that the biographical diversity from the age aspect in the Department of Economic Education showed the ideal age distribution, but the age range was so far that the generation Y employees was fewer than the generation X and the baby boomers, which implicated the increase of the workload of generation Y. This phenomenon often became an undisclosed internal conflict. From the aspect of sex in the Department of Economic Education, the number of male employees was 23 and the number of female employees was 21. From years of service, it was 1 year to 20 years. The findings of this study indicated that age range which implicated employee workloads and sex differences were not part of discrimination. Keywords: management, diversity, multicultural management, biographical diversity